1976
DOI: 10.1104/pp.58.4.499
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Reductase Activity in Maize (Zea mays L.) Leaves

Abstract: The roles that leaf nitrate content and nitrate flux play in regulating the levels of nitrate reductase activity (NRA) In certain experiments, root systems were rapidly (2 min) cooled while shoots remained at growth temperatures. Hoagland solution (8 C) was poured through the Vermiculite until the desired root temperature was reached. The cold-treated pots were then placed into copper coils through which water (3 C) was circulated. Temperature was regulated at 13.5 ± 0.5 C in the root medium by controlling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
1
5

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(96 citation statements)
references
References 17 publications
8
82
1
5
Order By: Relevance
“…These results agree with those reported by Shaner & Boyer (1976) and Reed & Hageman (1980), which indicate that nitrate flux and NRA are closely related. Other workers (Conejero et al, 1986) have shown that the addition of 4 mM NOg" to nodulated soybeans depressed leaf NRA in comparison with that of nonnodulated plants.…”
Section: Leaves (A) Stems (B) Roots (C) and Nodules (D) Of Foursupporting
confidence: 82%
“…These results agree with those reported by Shaner & Boyer (1976) and Reed & Hageman (1980), which indicate that nitrate flux and NRA are closely related. Other workers (Conejero et al, 1986) have shown that the addition of 4 mM NOg" to nodulated soybeans depressed leaf NRA in comparison with that of nonnodulated plants.…”
Section: Leaves (A) Stems (B) Roots (C) and Nodules (D) Of Foursupporting
confidence: 82%
“…There is some compensation for this impairment by the apparent greater induction of NRA in NaNO3 roots than in KNO roots. The maintenance of high NRA depends on a continuous N03 flux (1,19,20). The high NRA in NaNO3 roots is then the result of N03-absorption at a rate much faster than N03-translocation to leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Blevins et al (4) showed that in roots of barley seedlings treated with Ca(NO3)2, N03-accumulation, organic acid accumulation, and NRA were much less than in KNO3-treated seedlings. Shaner and Boyer (19,20), by using NO3 depletion and cooling of roots and water stress, showed that the decrease in leaf NRA was due to decreased N03 flux to leaves. In wheat seedlings treated with NaNO3, N03-translocation and accumulation were low unless the seedlings had been given a pretreatment with K+ (8).…”
Section: Resultsmentioning
confidence: 99%
“…6A). Although in vitro measurements of NR activity may not indicate the actual rate of nitrate assimilation in situ, NR is an inducible enzyme, the activity of which is related to the flux of nitrate through metabolic pools (20). Assuming that the in vitro assays indicate the potential for nitrate reduction in plant tissue (22), the responses of the shoot and root reductase systems to changing nitrate supply (Table I) appear to be consistent with the increased levels of nitrate detected in the xylem stream.…”
Section: Plant Materials and Experimentationmentioning
confidence: 99%